2014
DOI: 10.1007/s11892-014-0537-6
|View full text |Cite
|
Sign up to set email alerts
|

Is There an Association Between Diabetic Neuropathy and Low Vitamin D Levels?

Abstract: In the past few years, the effects of vitamin D that go beyond its relationship with bone metabolism have come into the focus of scientific attention. Research concerning diabetes and its complications has become a public health priority. An increasing number of reports link vitamin D deficiency to diabetes; however, so far, there has only been limited and contradictory data available on the correlation between diabetic peripheral neuropathy and vitamin D. Studies of people with type 2 diabetes confirmed the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 34 publications
0
14
0
4
Order By: Relevance
“…There is also recent evidence of a significant association between low vitamin D and impaired heart rate variability [85]. At present, there is growing interest in the contribution of vitamin D to the prevention of DSPN [86,87] and peripheral artery disease [88].…”
Section: Low Vitamin Dmentioning
confidence: 99%
“…There is also recent evidence of a significant association between low vitamin D and impaired heart rate variability [85]. At present, there is growing interest in the contribution of vitamin D to the prevention of DSPN [86,87] and peripheral artery disease [88].…”
Section: Low Vitamin Dmentioning
confidence: 99%
“…A number of clinical and animal studies have also examined the role of vitamin D in the pathogenesis of DPN. Although the findings have been inconsistent and occasionally contradictory, they have linked serum vitamin D levels with DPN [6,7]. The mechanisms that underpin the associations between vitamin D levels and DPN are not fully understood [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Although the findings have been inconsistent and occasionally contradictory, they have linked serum vitamin D levels with DPN [6,7]. The mechanisms that underpin the associations between vitamin D levels and DPN are not fully understood [6,7]. Pain sensitivity associated with low vitamin D levels may be directly mediated by its action on the dorsal root ganglia, specifically small nerve fibres [8].…”
Section: Introductionmentioning
confidence: 99%
“…There are very few studies on further protective biomarkers for diabetic sensorimotor polyneuropathy, but there is evidence that suggests there are reduced systemic levels of vitamins D and E in diabetic neuropathy [15,16]. One study reported reduced levels of epidermal growth factor in people with diabetic sensorimotor polyneuropathy [17].…”
Section: Discussionmentioning
confidence: 99%